Laser and Material Parameter Dependence of the Chemical Modifications in the UV Laser Processing of Model Polymeric Solids. Issue 1 (2002) - Andreou, E.; Athanassiou, A.; Fragouli, D.; Anglos, D.; Georgiou, S.
Abstract : Chemical modifications are expected to be the major type of side-effect in the UV laser processing of molecular substrates. For their systematic characterization, studies on polymeric systems consisting of poly(methyl methacrylate) and polystyrene films doped with aromatic dopants exemplifying different degrees of photoreactivity are undertaken. In particular, the dependence of the nature and extent of the modifications on chromophore properties and laser parameters (laser fluence, wavelength, and number of pulses) is examined. The substrate absorptivity and the number of employed laser pulses turn out to be the critical parameters in determining the quantity and nature of photoproducts that remain in the substrate. The implications of these results for the optimisation of laser processing of molecular/organic solids are discussed. It is suggested that the importance of employing relatively strongly absorbed wavelengths in laser processing may relate, besides the efficient etching and good surface morphology, to the minimization of the chemical modifications. In contrast, irradiation with successive laser pulses is indicated to be highly disadvantageous for the chemical integrity of the substrate. In all, the study of such model systems appears to be most appropriate for establishing criteria for the systematic optimisation of laser processing techniques of molecular substrates.